Argumentasi Keluarga berencana dalam Hukum Islam (Studi Fatwa Syaikh Mahmud Syaltut) - Irawan, Ibnu; Nasrullah, Nasrullah (JURNAL JAWI, 2020)
This according to the perspective of Mahmud Syaltut when there is an agreement there is no need to be disputed and there are new opinions. Mahmud SyaltutAbout Family Planning. This research is a library research study or library research, that is research conducted through data collection or scientific papers with research objects or data collection that is. The results of the study show that Family Planning (KB) law, so that this research can be developed for the benefit of a wider range of family planning programs that will be able to sort the desired community groups, so that the number must be increased and undesirable community groups so that the number must control. The implementation of the Family Planning (KB) program must be based on good intentions and the Implementation of Family Planning (KB) must be in accordance with Islamic Law.